The grammar of greatness' : self, community, and inspiration in Oliver St. John Gogarty - Goodspeed, Andrew (Trinity College (Dublin, Ireland). School of English, 2002)
The first chapter of this thesis is introductory, and proposes a reading of Oliver Gogarty as a self-depicting writer, one who usually employs the form of memoir. It argues that Gogarty does not demonstrate the confessionality and self-assessment usually associated with autobiography. The chapter reads Gogarty's self-depictions as attempting to communicate the subjective experiences of nobility, transcendence, and connection with timeless human values, that he derived from interaction with his most distinguished and colourful friends. The second chapter assesses Gogarty's poetry in light of his self-representations therein. It notes that he associates the qualities of transcendence and ennoblement with poetry that he finds in his friendships. The chapter observes that Gogarty rarely represents himself factually in his poetry, and that his representations of his life in his verse are primarily records of moments of spiritual transcendence. The third chapter studies As I Was Going Down Sackville Street, and argues that Gogarty's self-representation therein is that of a guide revealing Dublin 'as it is every day.' The chapter notes that this communal depiction is, in fact, really a depiction of the most accomplished figures in Ireland at the time, and that Gogarty represents his interaction with them as leading him backwards in time towards a spiritual 'Golden Age.' The fourth chapter reads I Follow Saint Patrick as one of Gogarty's most unusual self-depictions: it suggests that he here places himself into a textual relation with his exemplary figure (Patrick) in a manner that inverts his similar presentation of inspiration in Sackville Street. In I Follow Gogarty proposes another temporal regression of the spirit towards the timeless qualities of dignity and reverie he believes Patrick still represents for the Irish. The chapter notes that this is as much a political as a cultural regression, for it is a spurning of de Valera's era, and policies. The fifth chapter reads Tumbling in the Hay as a variation upon the Bildungsroman. In Fumbling, Gogarty presents a juxtapositional portrait of the society of Trinity College in his youth, and argues that community and social interaction are those experiences that both form the mind, and uplift one from the cares and boredoms of the everyday. He illustrates this by contrasting the dons and the students. The sixth chapter examines Gogarty's second clearly fictionalized memoir, Going Native. Going Native is Gogarty's first self-depiction set almost entirely outside of Ireland, and the chapter observes the shifting importance of community as the Gogarty figure attempts to attain the spiritual transcendence he seeks, whilst simultaneously repressing his spiritual exuberance in imitation of the English. It notes also that here his self-depiction is demonstrably incorrect as a representation of his life, and suggests that this novelization of his memories and experiences conflicts with the work's more serious attempt to provide social commentary contrasting English and Irish societies. The seventh chapter addresses Gogarty's life and work in the United States. It notes that Gogarty's work alters in America to accommodate the demands of periodical publications for which he wrote, which resulted in his writing short essays and memoirs about his friends from Ireland. The chapter notes that Gogarty's self-depictions in the United States portray a man incapable of forming the personal and social associations that he praises most highly in his Dublin writings. The chapter argues that Gogarty's continued reliance upon his memories of the Ireland of 1900-1939 is not, however, mere creative exhaustion, but is the inescapable result of his continued attempt to portray those friendships and associations by which he derived the greatest sense of ennoblement and spiritual transcendence. The people who provided him with these sensations were almost exclusively his companions in Ireland, between the years of 1900-1939. The eighth chapter notes that Gogarty positioned himself in American literary circles as one who had intimate biographical experience of the great Irish authors. The chapter asserts that Gogarty's late writings on Joyce associate his objections to Modernism with his bitter memories of Joyce, and that his late essays on Joyce thus support attacks on Modernism with the evidence of personal memory. This was problematic for Gogarty, for he had, throughout his self-depictions, argued that memory and friendship inspire one to transcend the facts of the everyday. His critics attacked him for being careless of fact. The chapter argues that his Joyce essays are consistent with his treatment of memory, fact, and spiritual reaction to another, and that they cannot be held to be mendacious when seen in the light of his previous self-depictions. The ninth chapter is a conclusion.
Keywords: English, Ph.D.; Ph.D. Trinity College Dublin